Respon Mahasiswa Agroteknologi Terhadap Pembelajaran Daring Pada Mata Kuliah Ekologi Tanaman - Vonnisye Vonnisye (LPPM UKI Toraja, 2021)
Online learning conducted in UKI Toraja Agrotechnology Study Program is one technique to cut off the spread of the pandemic Covid-19. Changes in this learning model certainly have an impact on the implementation of the learning process. Therefore, the purpose of this study was to determine the response of agro-technology students to online learning in plant ecology courses. This research is a descriptive study that is analyzed quantitatively and qualitatively. Data collection using a questionnaire filled out via google form. The results of the study concluded that 1) aspects of teaching materials were included in the very good category, 2) aspects of implementing online learning and aspects of student readiness were included in the good category, 2) aspects of motivation and problems were included in the sufficient category. These results imply that online learning in plant ecology courses is still not optimal and needs to be improved.